2002
DOI: 10.4049/jimmunol.169.1.55
|View full text |Cite
|
Sign up to set email alerts
|

2B4 Is Constitutively Associated with Linker for the Activation of T Cells in Glycolipid-Enriched Microdomains: Properties Required for 2B4 Lytic Function

Abstract: 2B4 is a receptor belonging to the Ig superfamily and is found on all murine NK cells as well as a small subset of T cells. Previous studies have found that cross-linking of the 2B4 receptor results in both increased cytotoxicity and IFN-γ secretion. We have discovered that 2B4 from transfected NK and T cell lines, as well as from primary murine cells, coimmunoprecipitates with the phosphoprotein linker for the activation of T cells (LAT), which is essential for TCR-mediated signaling. This association is inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
1
42
1
Order By: Relevance
“…Although one study reported that CD244 coprecipitated with Grb2 (40), we did not detect binding of these two molecules in our system. That interaction may be mediated by the linker for the activation of T cells, which has been reported to associate with CxC cysteine motif found in the transmembrane region of CD244 (41). The cytoplasmic tail of CS1 has a similar, putative Grb2 binding to the one found in CD229, but we were unable to detect any interaction between these two proteins.…”
Section: Discussionmentioning
confidence: 53%
“…Although one study reported that CD244 coprecipitated with Grb2 (40), we did not detect binding of these two molecules in our system. That interaction may be mediated by the linker for the activation of T cells, which has been reported to associate with CxC cysteine motif found in the transmembrane region of CD244 (41). The cytoplasmic tail of CS1 has a similar, putative Grb2 binding to the one found in CD229, but we were unable to detect any interaction between these two proteins.…”
Section: Discussionmentioning
confidence: 53%
“…CD244-mediated signaling is also influenced by the transmembrane domain of the receptor through its constitutive association with LAT in humans (18) and mice (19). However, CD244-mediated signaling is not influenced by the transmembrane or extracellular domains of the receptor, but rather it is defined solely by tyrosine-based motifs in the cytoplasmic tail (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that CD244 and SAP colocalize to the immunological synapse upon the formation of conjugates between NK cells and target B cells and this finding highlights the role of CD244-SAP complex during the NK cellmediated control of EBV infection (17). CD244 has also been found to associate constitutively with the adaptor molecule LAT via a dicysteine motif (CxC) located in the transmembrane domain of CD244 (18,19). In this paper, we describe a novel interaction between CD244 and the adaptor protein 3BP2 in NK cells and show that 3BP2 links CD244 to downstream events regulating the cytotoxic function of CD244 without affecting IFN-␥ secretion.…”
mentioning
confidence: 86%
“…Indeed, two previous studies describe an interaction of human 2B4 with LAT [40,41]. Another study detected an association of mouse 2B4 with LAT and described the importance of the CXC motif for this interaction [36]. CSS-PALM 3.0 recognized the CXC motif in 2B4 as a likely site of palmitoylation [37].…”
Section: Discussionmentioning
confidence: 94%
“…4E and G). A previous study of mouse 2B4 suggested that the "CXC" motif contained within the LACFCV sequence is important for an association with LAT and for 2B4-mediated effector functions [36]. Additionally, this "CXC" motif is recognized as a potential palmitoylation site by the palmitoylation software CSS-PALM 3.0 [37].…”
Section: Resultsmentioning
confidence: 99%